2007
DOI: 10.1128/jvi.00527-07
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Mediated Immunopathological Events Are Associated with Atypical Innate and Adaptive Immune Responses in Patients with Severe Acute Respiratory Syndrome

Abstract: It is not understood how immune inflammation influences the pathogenesis of severe acute respiratory syndrome (SARS). One area of strong controversy is the role of interferon (IFN) responses in the natural history of SARS.The fact that the majority of SARS patients recover after relatively moderate illness suggests that the prevailing notion of deficient type I IFN-mediated immunity, with hypercytokinemia driving a poor clinical course, is oversimplified. We used proteomic and genomic technology to systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
387
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(421 citation statements)
references
References 57 publications
(70 reference statements)
19
387
1
8
Order By: Relevance
“…In addition, IFN-γ antagonizes the anti-inflammatory effects of IL-10 either by attenuating IL-10 production, thereby inhibiting the TLR-induced Il10 gene expression or by suppressing IL-10 signaling [34]. Here we demonstrate that during acute illness, DBA/2J mice had increased macrophages recruitments and robust IFN-γ responses, as demonstrated by high-peak levels of the IFN-stimulated cytokines TNF-α and IL-6, which likely predispose them to more severe tissue injury [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IFN-γ antagonizes the anti-inflammatory effects of IL-10 either by attenuating IL-10 production, thereby inhibiting the TLR-induced Il10 gene expression or by suppressing IL-10 signaling [34]. Here we demonstrate that during acute illness, DBA/2J mice had increased macrophages recruitments and robust IFN-γ responses, as demonstrated by high-peak levels of the IFN-stimulated cytokines TNF-α and IL-6, which likely predispose them to more severe tissue injury [35].…”
Section: Discussionmentioning
confidence: 99%
“…In case of coronavirus infection, either MERS-CoV or SARSCoV, it was observed that virus infection induces an excessive activation of the immune system which leads to the synthesis of several pro-inflammatory cytokines like interleukin-1beta (IL-1B), IL-6, IL-8, CXC-chemokine ligand 10 (CXCL10), CC-chemokine ligand 2 (CCL2), and interferon-γ (IFN-γ) [9][10][11][12]. This proinflammatory response will ultimately induce pulmonary circulation capillary leakage which will lead to non-cardiogenic pulmonary edema, hypoxemia, type II pneumocyte hyperplasia, and neutrophil infiltration.…”
mentioning
confidence: 99%
“…IL-6 is considered to act as an endogenous pyrogen that regulates the synthesis of acute-phase proteins, including CRP. IFN-g regulates macrophage and NK cell activation, and might contribute to high fever and capillary leak syndrome [12], although hemophagocytosis was not seen in this case. Extremely high serum levels of IL-10 suggest that a compensatory anti-inflammatory process may play a role.…”
mentioning
confidence: 94%